Evaluation of a sanitizing system using isopropyl alcohol quaternary ammonium formula and carbon dioxide for dry-processing environments - Kane, Deborah M. (Kansas State University, 2012)
Dry-processing environments are particularly challenging to clean and sanitize because water introduced into systems not designed for wet cleaning can favor growth and establishment of pathogenic microorganisms such as Salmonella. The objective was to determine the efficacy of isopropyl alcohol quaternary ammonium (IPAQuat) formula and carbon dioxide (CO[subscript]2) sanitizer system for eliminating Enterococcus faecium and Salmonella on food contact surfaces. Coupons of stainless steel and conveyor belting material used in dry-processing environments were spot-inoculated in the center of 5 × 5 cm coupons with approximately 7.0 log CFU/ml of E. faecium and up to 10 log CFU/ml of a six-serotype composite of Salmonella and subjected to IPAQuat-CO[subscript]2 sanitation treatments using exposure times of 30 s, 1 or 5 min. After sanitation treatments, wet coupons were swabbed for post-treatment survivors. Preliminary experiments included coupons which were soiled with a flour and water solution prior to inoculation and subsequent sanitation treatments. For the main study, inoculated surfaces were soiled with a breadcrumb flour blend and allowed to sit on the lab bench for a minimum of 16 h before sanitation. Preliminary results showed that IPAQuat-CO[subscript]2 sanitizing system was effective in reducing approximately 3.0 logs of E. faecium and Salmonella from clean and soiled surfaces after 1 min exposure but higher initial inoculum levels were needed to demonstrate >5 log reductions. For the main study, pre-treatment Salmonella populations were approximately 7.0 log CFU/25 cm[superscript]2 and post-treatment survivors were 1.3, < 0.7 (detection limit), and < 0.7 log CFU/25 cm[superscript]2 after 30 s, 1 or 5 min sanitizer exposures, respectively, for both clean and soiled surfaces. Treatment with IPAQuat-CO[subscript]2 sanitation system using 30 s sanitizer exposures resulted in 5.7 log CFU/25 cm[superscript]2 reductions whereas, greater than 6.0 log CFU/25 cm[superscript]2 reductions were observed for sanitizer exposures of 1 and 5 min. The IPAQuat-CO[subscript]2 sanitation system reduced 6 logs CFU/25 cm[superscript]2 of Salmonella with sanitizer exposure times of at least 1 min. The IPAQuat-CO[subscript]2 system would, therefore, be an effective sanitation system to eliminate potential contamination from Salmonella on food contact surfaces and have application in facilities that process dry ingredients or low-moisture products.
Keywords: Sanitizing system; Sanitizers; Salmonella; Dry-processing; Isopropyl alcohol; Quaternary ammonium compounds; Food Science (0359)